Village Farmer Community Empowerment Efforts (Study of Farmer Social Capital in the Pesantren Petani Nusantara Program, Pangandaran Regency) - Widaty, Cucu (LPPM Universitas PGRI Sumatera Barat, 2023)
This study describes the community empowerment program for farmers through Pondok Pesantren Petani Nusantara program. This is motivated by the lives of people who are experiencing various problems, such as shifting farmers' livelihoods, the number of poor farmers, and also the low education of farmers who are not yet empowered and not independent. The research method used is a descriptive method with a qualitative approach. The subjects in this study were program managers, farmers and program participants, as well as the government. The results of this study can be seen that the beginning of the establishment of the Pondok Pesantren Petani Nusantara program in 2004 was the idea and aspiration of the farmers in the village of Pangandaran who wanted to advance their potential to be more advanced and prosperous. This is proven by the three excellent programs that continue to develop until now, namely the Prosperous Farmers Group (KTS), Women's Farmer Group (KWT), and Youth Farmer Training (PATRA). In implementing programs such as the farmers' program, they are less concerned and do not support the program, farmers who have other activities cannot be carried out in the meeting program, and there are also disputes that cause a lack of farmer participation. The benefits of farmers are an increase in the economy, an increase in the number of farmers, a stronger sense of solidarity in farming, an increase in knowledge and skills, and an increase in livelihoods or urbanization. The government actively supports the program by providing various facilities and infrastructure, as well as conducting monitoring and evaluation.